Brent Geese in Essex - The proportion of first-winter birds in flocks of Brent Geese in Essex - Burton, P J K (Wildfowl, 1957)
During the past three winters (1954-55, 1955-56, 1956-57), regular counts have been made of the number of first-winter birds in flocks of Dark-bellied Brent Geese (Branta b. bernicla) on the Essex coast. In this way it is hoped to keep a check on breeding success from year to year. Such a check is particularly desirable for this species. The reported diminution of its numbers has aroused much concern, and at present it is enjoying a trial period of full protection. The counts have also yielded information on the behaviour and movements of feeding flocks.